ADIPOSITY AND RISK OF HYPERTENSION OF THE JUDO ATHLETES (Fiep Bulletin - online, 2014)
The Judo uses the weight/age to separate in categories. Actions for the improvement in the performance are very frequents can be obtained by lighter category changing, who generates risk of dehydration and loss of muscle mass, that will go to harm, beyond the health the competitive performance. The objective of this study was to verify the body composition of the athletes of Maringá/PR and to analyze if this if relates with factors of risk for cardiovascular diseases. For this propose a sample of 20 male athletes with age of 18 years in the academies of Maringá was selected. A scale was used, a scientific calipter, a stethoscopes and a sphygmomanometer. The results had indicated a high prevalence of weight excess (overweight + obesity), with 60% of the sample in this condition. It was verified that this condition is related to a risk of hypertension and excess of adiposity. In this way, suggests that the teams receive the attention from professionals of physical education to accomplishment of periodic evaluations.
Keywords: judo; body composition; hypertension